Preprocedural Mouthrinses for Reducing Dental Cross-Infection: A Systematic Review and Meta-Analysis - Mi-Rim Yun; Na-Young Lee; Han-Na Kim (치위생과학회지, 2025)
Background: Dental procedures result in the production of aerosols, which increase the risk of cross-infection in both patients and healthcare workers. This study investigated the effect of mouthrinsing on the aerosol microbial load, considering the type of mouthrinse used and the placement of collection media. Methods: A meta-analysis was performed on studies published between January 2000 and August 2022, in accordance with PRISMA guidelines. Standardized mean differences (SMDs) and 95% confidence intervals (CIs) were calculated and compared. Results: Of the 1,039 articles identified, 42 and 7 met the review and meta-analysis criteria, respectively. The six mouthrinses tested were chlorhexidine, herbal mouthrinse, ozonated water, povidone-iodine, boric acid, and chlorine dioxide. Chlorhexidine (SMD –8.13; CI –11.87, –4.40) and the remaining five mouthrinses (SMD –5.42; CI –7.73, –3.11) achieved significantly greater microbial reduction than that achieved using distilled water. Chlorhexidine mouthrinses showed a greater effect size than the other five mouthrinses (SMD –2.91; CI –4.51, –1.32). The reduction in the patient’s chest (SMD –7.74; CI –11.11, –4.38) was greater than in the operator’s chest (SMD –5.56; CI –8.15, –2.98). Thus, mouthrinses reduced the microorganism content of aerosols, with reductions depending on mouthrinse type and collection media placement. Conclusion: The findings suggested that preprocedural rinsing is essential for infection control in dentistry and enhanced the occupational health safety of dental professionals.